The outlook for the Euro : lessons from the DEM - Sweeney, Richard J. (Economics and Business Review, 2005)
The Euro started at 1.19 but has fallen as low as 0.82 and risen as high as 1.35. If the Euro behaves like the DEM, the long run value of the Euro is approximately 1.00, and over time, the Euro is likely to rise as high as 1.552 and fall to as low as 0.645. Many have criticized the European Central Bank, often severely, first because the Euro weakened greatly during most of its first three years, starting in January, 1999, and then because it strengthened greatly over the next three years. The Euro has been less volatile so far than the DEM was over the floating period starting in March, 1973; by this standard, the ECB has done as well as the Bundesbank did, and the Bundesbank was acknowledged as by far the best performing European central bank. Based on the record of the DEM, if the new members of the European Union adopt the Euro, they are in for substantial exchange-rate volatility; adopting the Euro may still make a great deal of sense if the new members cannot trust their own central banks to run low-inflation policies. (original abstract)